Laxative effect and mechanism of Tiantian Capsule on loperamide-induced constipation in rats. (10th February 2021) - Li, Tian; Hu, Mengmeng; Jiang, Cuihua; Zhang, Dongjian; Gao, Meng; Xia, Jianwei; Miao, Mengqi; Shi, Gaofeng; Li, Hui; Zhang, Jian; Yin, Zhiqi
Abstract: Ethnopharmacological relevance: Tiantian capsule (TTC), as a functional food, which consists of four herb medicines, including Aloe vera Burm.f. (25%), leaf juices, dried; Cucurbita moschata Duch. (25%), fructus, dried; Poria cocos (Schw.) Wolf. (12.5%), sclerotium, dried; Tremella fuciformis Berk. (12.5%), fruiting bodies, dried, and one extract xylooligosaccharides (25%) from Maize Cob by enzymolysis, has been commonly used in China to ameliorate constipation. Aim of the study: The aim of the work is to elucidate the potential laxative mechanisms of TTC in loperamide-induced constipated rats. Materials and methods: LC-MS/MS was employed for analyzing the TTC extract. The gastrointestinal transit was evaluated by X-ray. The H&E and Alcian-Blue stain were applied to determine the changes of goblet cells and mucus layer, respectively. Meanwhile, levels of neurotransmitters were evaluated by enzyme-linked immunosorbent assay. The protein expressions were also measured by immunohistochemistry and Western blot. Results: Our results showed that TTC administration attenuated constipation responses in aspects of fecal pellets number, water content of feces, stomach emptying and gastrointestinal transit. Further investigations revealed that TTC treatment not only induced the recovery of neurotransmitters, such as motilin, substance P, somatostatin, endothelin and vasoactive intestinal peptide, but also up-regulated the expressions of c-kit and stem cell factor (SCF). Additionally, the number of goblet cells and thickness of the mucus layer were elevated, and the guanylate cyclase C-cGMP signal pathway was also up-regulated after TTC treatment. Conclusion: Our findings demonstrated that the laxative effect of TTC in constipation rats is probably due to the regulation of bowel movement and intestinal fluid secretion.